Effects of red and blue light on growth and photosynthesis of Populus szechuanica var. tibetica - Xu, Rong; Zhang, Shihai; Wang, Cai; Zhang, Xiaolin; Zhao, Lihong; Zong, Dan (Frontiers in Plant Science, 2025)
IntroductionPopulus szechuanica var. tibetica is a high-altitude tree species. At elevated altitudes, the proportion of short-wave light increases, suggesting that P. szechuanica var. tibetica has likely evolved unique adaptive mechanisms to withstand such conditions.MethodsIn this study, one-year-old P. szechuanica var. tibetica branches were cultivated in seedling bags and subjected to different light treatments: white light (W control), monochromatic red light (R), and mixed red-blue light (B) systems with varying ratios (R1B3, R3B1), to investigate the effects of red-blue light quality on P. szechuanica var. tibetica morphology, leaf anatomical structure, photosynthetic performance, and photosynthetic metabolism.ResultsThe results demonstrated that monochromatic red light enhanced P. szechuanica var. tibetica growth and leaf expansion while reducing photosynthetic efficiency. In contrast, mixed red-blue light treatments - particularly the R1B3 ratio - induced a compact growth morphology with thicker, smaller leaves. These structural modifications corresponded with improved adaptation to high-altitude environments where short-wave light constitutes a greater proportion of the solar spectrum. In terms of photosynthetic characteristics, R1B3 enhances photosynthesis in P. szechuanica var. tibetica through a synergistic effect of increasing the number of stomata on the upper epidermis of leaves and improving stomatal conductance, as well as significantly increasing Rubisco activated enzyme (RCA) content and Rubisco activity. Collectively, P. szechuanica var. tibetica under R1B3 light treatment adapt to altered light quality by modifying their growth morphology, leaf anatomy, and photosynthetic metabolites, resulting in enhanced photosynthetic efficiency.DiscussionThis study provides theoretical support for the adaptation mechanism of P. szechuanica var. tibetica to different light qualities, but the ratio of red to blue light qualities needs further refinement. In subsequent research, the ratio can be refined and the proportion of blue light increased to deepen the study.